2022
DOI: 10.52689/higea.v14i1.450
|View full text |Cite
|
Sign up to set email alerts
|

Skrining Fitokimia dan Aktivitas Antibakteri Ekstrak Bawang Putih Tunggal terhadap Staphylococcus aureus

Abstract: Resistensi antibiotika yang meningkat dapat dihambat dengan cara menggunakan antibiotik secara rasional dan mengembangkan sediaan bahan alam yang ada sebagai alternatif pengobatan. Salah satu bahan alam yang dapat dimanfaatkan adalah bawang putih tunggal atau bahasa ilmiahnya adalah Allivum sativum Linn. Beberapa penelitian menyebutkan bahwa bawang putih tunggal memiliki berbagai manfaat, salah satunya sebagai antibakterikarena kandungan allicin, namun masih sedikit literatur yang melakukan penelitian terkait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
9
0
3
Order By: Relevance
“…These three types of spices have been widely reported to have the ability to prevent microbial contamination in foodstuffs. The method of marinating fish tuna meat with the three seasoning ingredients (garlic, chili, and asam sunti) does not only protect the fish tuna meat against microbial contamination, but also improve the flavour, the texture, the taste and the overall consumer preference of the marination fish tuna meat [4,5,6,7,8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These three types of spices have been widely reported to have the ability to prevent microbial contamination in foodstuffs. The method of marinating fish tuna meat with the three seasoning ingredients (garlic, chili, and asam sunti) does not only protect the fish tuna meat against microbial contamination, but also improve the flavour, the texture, the taste and the overall consumer preference of the marination fish tuna meat [4,5,6,7,8].…”
Section: Resultsmentioning
confidence: 99%
“…Some spices that have the potential to preserve food are garlic (Allium sativum L.) [3], green cayenne pepper (Capsicum frutescens L.) [4], pepper (Piper nigrum L.) [5] and asam sunti (salt fermented fruit of Averrhoa bilimbi) [6]. Based on several research results, it was found that these spices or seasonings have an influence on the preservation of food and used to improve the flavour of the food [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids, alkaloids, and terpenoids were able to inhibit the growth of S. aureus by preventing nucleic acid synthesis, energy formation, inhibiting the formation of FabZ and fimbriae enzymes (Khusnia, 2020); Pudiarifanti & Farizal 2022). The presence of flavonoids in the ethanol extract of red onion skin was proven in the study of Setiani et al (2017) who reported that the levels of flavonoids extracted by the maceration method were 14.92%, while the MAE (Microwave Assisted Extraction) method was 17.18%.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Adanya flavonoid ditunjukan dengan terbentuknya warna merah, kuning, atau jingga pada lapisan amil alkohol. Tabung II digunakan sebagai sampel pembanding (Pudiarifanti & Farizal, 2022).…”
Section: Pembuatan Ekstrakunclassified